2015
DOI: 10.1021/acs.macromol.5b00173
|View full text |Cite
|
Sign up to set email alerts
|

Membranotropic Peptide-Functionalized Poly(lactide)-graft-poly(ethylene glycol) Brush Copolymers for Intracellular Delivery

Abstract: A biodegradable delivery scaffold based on poly(lactide)-graft-poly(ethylene glycol) (PLA-g-PEG) is introduced and tested in vitro. The use of a functional ring-opening polymerization initiator (containing a masked aldehyde) on an azido PEG-lactide monomer combines two known methodologies to afford functionalized PLA. The resulting copolymer features two compatible functional groups and decreased hydrophobicity due to the PEG. The functional groups are capable of performing high-yielding orthogonal postpolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Overall yields for the synthetic strategy of A58-A60 were 6-16%. Weck and coworkers 139 introduced an azido-tri(ethylene glycol) functional lactide (A61). Polymers were modified with a fluorescent dye (7-nitrobenzoxadiazole, NBD) and a cell internalization peptide gH625 by click chemistry, and proved cellular uptake.…”
Section: Review Article Chem Soc Revmentioning
confidence: 99%
“…Overall yields for the synthetic strategy of A58-A60 were 6-16%. Weck and coworkers 139 introduced an azido-tri(ethylene glycol) functional lactide (A61). Polymers were modified with a fluorescent dye (7-nitrobenzoxadiazole, NBD) and a cell internalization peptide gH625 by click chemistry, and proved cellular uptake.…”
Section: Review Article Chem Soc Revmentioning
confidence: 99%
“…10,11 This peptide has proved to exhibit exceptional vector properties 9 and has been shown to be essentially internalized by a nonendocytic pathway avoiding endosomal entrapment. 7,[12][13][14][15][16][17] In recent studies, it was also shown to be able to cross the blood-brain barrier in vitro and in vivo. 18 gH625 is, therefore, a very good delivery vector 9 and its coupling to NPs may be exploited to change their internalization mechanism and in case of MNPs, to avoid or reduce their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the development and use of alternative, metal‐free click strategies. Diels‐Alder, strain‐promoted cycloadditions, and thiol/ene reactions have all been used with respect to polymer functionalization. Dove and coworkers have recently utilized all three of these reactions in an orthogonal, one‐pot, postpolymerization strategy for the preparation of functional polycarbonates …”
Section: Introductionmentioning
confidence: 99%